Evaluation of Spasticity Variations at the Elbow Joint of CVA Patients According to the Biomechanical Indices - Nima Soleimanzadeh-Ardabili; Iman Vahdat; Iraj Abdollahi; Mostafa Rostami (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The goal of the present study was to evaluate spasticity variations by increase the velocity of motion and MAS value in the elbow flexor and extensor muscles at extension and flexion of CVA patients elbow joint according to the biomechanical indices. Materials & Methods: Fifteen adult patients with a history of stroke and upper-extremity spasticity volunteered to participate in this study and fifteen healthy subjects were recruited in order to establish the control group. The degree of spasticity was evaluated for each patient using the MAS. CPM tests were imposed in elbow extension and flexion and the biomechanical indices were calculated at each of the following velocities: 15, 45, 75 and 120 º/s. Results: It seemed a regular increment of the viscoelastic and viscose stiffness indices by increasing the velocity of motion and the rate of MAS value in both extension and flexion in all test groups and also there was significant regular increment of elastic stiffness index by increasing the velocity in both extension and flexion between the control group and group 1 and also irregular increment between group1 and group 2 and 3 and also the effect of mentioned index was decreased at higher level of MAS. Conclusion: it seemed the more effect of elastic stiffness in spasticity in CVA patients at lower level of MAS and more effect of viscose stiffness in higher level of MAS and also results showed the increment of viscose stiffness by increment of speed of motion and the rate of MAS.